2020
DOI: 10.1080/19407963.2020.1839088
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of host-city residents of the impact of mega-events and their support: the EXPO 2020 in Dubai

Abstract: Events tourism has been growing rapidly and has become one of the most common ways of attracting tourists to developing destinations. Hosting mega-events has become a means to achieve rapid development in a destination. Host-city residents are the first to feel the impact of hosting such events and are considered as key stakeholders. Results from a survey distributed in Dubai revealed that residents supported the upcoming EXPO 2020 event, with little concern for the potential associated costsa result contradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(169 reference statements)
1
11
0
Order By: Relevance
“…This research finding contrasts evidence provided by recent studies on the importance of negative externalities of trade fair activity (Fredline et al , 2005; Mensah, 2012). However, the research findings of this paper concur with the results of other studies indicating that residents of the host cities support trade fairs without being significantly concerned about environmental implications, including traffic congestion and air pollution (Al Hallaq et al , 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This research finding contrasts evidence provided by recent studies on the importance of negative externalities of trade fair activity (Fredline et al , 2005; Mensah, 2012). However, the research findings of this paper concur with the results of other studies indicating that residents of the host cities support trade fairs without being significantly concerned about environmental implications, including traffic congestion and air pollution (Al Hallaq et al , 2021).…”
Section: Discussionsupporting
confidence: 89%
“…As with any event that attracts a large number of visitors to a relatively small area in a short period of time, disturbance is likely to be a result of increased traffic, noise and crowding, while a higher level of pressure can be placed on the natural and human environment (Fredline et al, 2005). However, Al Hallaq et al (2021) show that residents in some cases support the events without being concerned about negative implications, such as increased traffic. Moreover, any excess supply created during the preparation phase needs to be eliminated after the end of the trade fair; otherwise, the region may face economic recession (Aydogus et al, 2015).…”
Section: Trade Fair Effectsmentioning
confidence: 99%
“…SET predicts that positive perceptions of tourism impacts can translate into positive opinions of tourism and support for tourism (Ap, 1992; Látková & Vogt, 2012; Pizam, 1978). However, it is unclear how generalisable the theory is in different international contexts, suggesting that further empirical research is needed (Al Hallaq et al, 2020;Olya, 2020; Olya & Gavilyan, 2016). SET measures actions that are based upon a rewarding reaction from others (Emerson, 1976) to provide economic analysis of non‐economic situations (Homans, 1974).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If residents differentiate between tourism and tourists, it is also possible that they differentiate between types of impact. Economic impacts, for example, may be seen as more significant, whilst social impacts may be less so (see Al Hallaq et al, 2020). Negative perceptions of "less important" impacts will not counter-act positive perceptions from "more important" impacts.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…Recent studies have shown that involvement with mega-events can affect attitudes toward the event (e.g. satisfaction, support) (Al Hallaq et al, 2020;Davies & Jaimangal-Jones, 2020). Other studies have shown that involvement with a product can affect attitudes toward values.…”
Section: Involvement With Olympic Gamesmentioning
confidence: 99%